PENGARUH KWALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PT KAI DI STASIUN PURWOSARI SURAKARTA - LAKSONO SUMARTO; SRI SAWITRI RAHAYU (Fakultas Ekonomi dan Bisnis UTP Surakarta, 2017)
The purpose of this study were (1) to examine and measure the extent to which the partial effect of reliability, responsivness, assurance, empathy, and tangible to Customer SatisfactionÂ in PT KAI Purwosari station of Surakarta. (2) To understand the interaction effect simultaneously between the reliability, responsiveness, empathy, and tangible to the customer satisfaction in PT KAI Purwosari station of Surakarta. This research was conducted at PT KAI in Purwosari Station of Surakarta. The number of respondents who selected as sample by purposive sampling technique was 100 respondents. The analysis used is multiple linear regression analysis. The research found that (1) There is a partial effect between reliability (reliability), responsiveness (responsivness), assurance (assurance), empathy (empathy) and tangibles (tangible) towards customer satisfaction in PT KAI Purwosari station of Surakarta. (2) There is a simultaneous effect of reliability, responsiveness, assurance, empathy and tangibles to customer satisfaction in PT KAI Purwosari station of Surakarta. Customer satisfaction in PT KAI Purwosari Station can be explained by influenced of variable reliability, responsivness, assurance, empathy, and tangible amounted to 67.30% and the balance of 32.70% reflects the existence of other variables that are not observed in this study